PEMAKNAAN MOTIF TOKEK PADA KAIN TENUN UTAN WELAK MAUMERE - Feri Sanjaya (Oratio Directa (Prodi Ilmu Komunikasi), 2020)
Abstract Indonesia is known as a civilized nation. Including one of them the work of Maumere ikat. The cloth comes from Flores, which has high artistic value and is beautiful. In general, woven ikat maumere fabric is fabric made from weaving processes that require so much energy and time. Maumere ikat is also made by women who have high creativity and artistic creations. Maumere's ikat weaving is not only limited to artistic creations, but its making also considers symbols of social, religious, cultural and economic status. Even certain motifs are made through high concentration of thought. This research is related to the meaning of motifs in Welak Maumere Ikat Weaving cloth with Gecko motifs. The meaning of the "WELAK" ikat motifs in Sikka is called "UTAN" which represents something of value. Keywords: Meaning, Gecko Motif, Welak Woven Fabric  Abstrak Indonesia dikenal sebagai bangsa yang berbudaya. Termasuk salah satunya hasil karya berupa tenun ikat Maumere. Kain tersebut berasal dari Flores yang bernilai seni tinggi dan indah. Pada umumnya kain Tenun ikat maumere adalah kain yang dibuat dari proses menenun yang memerlukan tenaga dan waktu yang begitu lama. Tenun ikat Maumere juga dibuat oleh kaum perempuan yang memiliki daya cipta dan kreasi seni yang tinggi. Tenun ikat Maumere  juga bukan hanya sebatas kreasi seni, tetapi pembuatannya juga mempertimbangkan simbol status sosial, keagamaan, budaya dan ekonomi. Bahkan beberapa motif tertentu yang pembuatannya melalui renungan konsentrasi tinggi. Penelitian ini terkait makna motif dalam kain Tenun Ikat Welak Maumere dengan motif Tokek. Makna motif tenun ikat “WELAK” yang dalam bahasa daerah Sikka disebut “UTAN” yang merepresentasikan sesuatu nilai.  Kata kunci : Pemaknaan, Motif Tokek, Kain Tenun Utan Welak